Tingkat Kesiapsiagaan Masyarakat Menghadapi Bencana Banjir - Zoya Salsabila Putri; Mushoddik (Jurnal Penelitian Pendidikan Geografi, 2022)
Kebon Pala is one of the areas located in Kampung Melayu Village, East Jakarta. In Kebon Pala, there are several RT dan RW dan some of them often flood until now. Areas that frequently flood in Kebon Pala are located in RT 12 dan RT 13. This study aims to determine the level of community preparedness in RT 12 dan RT 13 regarding flooding. This type of research uses descriptive quantitative method with 44 respondents. The data obtained from this study are primary dan secondary data. The results showed that the knowledge dan attitude parameter was the parameter with the highest index value (86.3), emergency response plan parameter (65.4), disaster warning system (75.9), supporting resources (51.3). Then if the total index is calculated, the result is 75.4. This researcher states that the community is “ready” in dealing with flood disasters.